(untitled) (Research, Society and Development, 2021)
Introduction: In dentistry there are several challenges and an aesthetic and functional rehabilitation of teeth with coronary destruction is one of them. General Objective: to elucidate a literature review regarding esthetic and functional rehabilitation with anatomical fiber pins. Methodology: For the construction of this scientific article, a descriptive bibliographic review of the literature was used. Results and Discussion: When presented cases where there is a great loss in the tooth structure, the use of fiberglass posts is presented as an excellent alternative offering better support to rehabilitate the unit. Conclusion: we conclude that the technique used brings concrete benefits for both the professional and the patient. Because it has a modulus of elasticity close to dentin, thus enabling a better distribution of loads, as well as the risk of fractures.